2018
DOI: 10.2196/jmir.9156
|View full text |Cite
|
Sign up to set email alerts
|

Young People’s Experiences of Viewing the Fitspiration Social Media Trend: Qualitative Study

Abstract: BackgroundSocial media use has become ubiquitous in the lives of many people, especially young adults. A popular recent trend emerging on social media is that of posting and following ‘Fitspirational’ content - material that purports to motivate and showcase healthy lifestyle habits, particularly relating to exercise and diet. There is very limited existing literature on how engaging with this type of content influences people’s psychological and physical heath. Initial studies have focused on concerns over po… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
41
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 20 publications
(26 reference statements)
4
41
0
2
Order By: Relevance
“…Blog authors translated healthy eating knowledge in simple terms by generating practical recommendations and ideas for the reader to implement in their everyday life. These findings are supported by a study investigating health and fitness social media use in young adults [48]. The study identified that readers sought and valued practical information and identified the use of social media as a supportive means to encourage behaviour change through the communication of practical information, which then inspired and motivated healthier behaviours [48].…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Blog authors translated healthy eating knowledge in simple terms by generating practical recommendations and ideas for the reader to implement in their everyday life. These findings are supported by a study investigating health and fitness social media use in young adults [48]. The study identified that readers sought and valued practical information and identified the use of social media as a supportive means to encourage behaviour change through the communication of practical information, which then inspired and motivated healthier behaviours [48].…”
Section: Discussionmentioning
confidence: 70%
“…The study identified that readers sought and valued practical information and identified the use of social media as a supportive means to encourage behaviour change through the communication of practical information, which then inspired and motivated healthier behaviours [48]. It has been reported that practical information communicated to readers by healthy eating blogs, including recipe ideas, tips to improve diet-related lifestyle issues and general healthy eating tips, are valued by readers and influence returned readership [7, 48]. The desire for practical information emphasises the importance of communicating procedural healthy eating information, rather than declarative [49].…”
Section: Discussionmentioning
confidence: 99%
“…The study indicated an association between fitspiration posting and drive for thinness, bulimia, drive for muscularity and compulsive exercise (Holland & Tiggemann, 2017). A study on male and female university students in the UK, found that social media posts on #Fitspiration on Instagram resulted in both positive (motivation and knowledge) and negative (feeling guilty about food choices) experiences (Easton et al, 2018), thus highlighting SM's ability to F o r P e e r R e v i e w rationalise disordered eating and over-exercise in campaigns which allegedly promote "healthiness" (Holland & Tiggemann, 2017).…”
mentioning
confidence: 99%
“…Previous literature has largely explored Facebook use and BI (Haferkamp & Krämer, 2011; Seidman & Miller, 2013; Thompson & Lougheed, 2012). There is now an increased focus on newer SNSs, such as Instagram, and how it affects users’ psychological and physical health (Easton et al, 2018). SNS influences BI and EB in a number of different ways; Mabe et al (2014) reported that total time usage influences BI and EB, with greater usage leading to more negative feelings, whereas Holland and Tiggemann (2016) found that the more engaged and active the user is with SNS, for example, by posting photos, the greater the negative effect.…”
mentioning
confidence: 99%
“…However, a cohort study conducted in Qatar among adolescent using the same questionnaire found a high significant difference in rating of unattractive or ugly feature(s), and for Distress caused by feature(s) was insignificant before and one year after procedure (10) . The reason might be because the adolescents have more concerns and experience inferiority regarding their appearance than adults (20) . Other study conducted in Saudi Arabia showed different result regarding appearance distress for patients undergone surgery as they rate it with good psychological scores meaning they have less appearance distress (21) .…”
Section: Discussionmentioning
confidence: 99%